2022
DOI: 10.1177/08884064221119166
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Service Time and Racial Categories within Traditional and Alternative Route Internship Programs for Special Education Licensure

Abstract: We used 14 years of state licensure and classroom data from Virginia to follow 19,878 special educaiton teachers (SETs) who completed either the alternative route (AR) internship or traditional programs. Findings reveal that a greater percentage of SETs of color participated in AR programs compared to traditional licensure programs, while a greater percentage of White SETs completed traditional programs. SETs of color attained approximately three fewer years of service time if they completed the AR program com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Student demographics were not reported. Wojcik et al (2023) reported that individuals from diverse backgrounds enter GYOs and alternative licensure programs at higher rates than traditional licensure programs, and alternative programs may successfully attract black men to the teaching profession (Scott, 2019). Although some alternative pathways are not associated with institutes of higher education, others, like LEAP, feature district and university partnerships (Brownell & Sindelar, 2016, no page;Podolsky et al, 2016;Zeichner, 2003).…”
Section: Preparing Diverse Sesmentioning
confidence: 99%
See 4 more Smart Citations
“…Student demographics were not reported. Wojcik et al (2023) reported that individuals from diverse backgrounds enter GYOs and alternative licensure programs at higher rates than traditional licensure programs, and alternative programs may successfully attract black men to the teaching profession (Scott, 2019). Although some alternative pathways are not associated with institutes of higher education, others, like LEAP, feature district and university partnerships (Brownell & Sindelar, 2016, no page;Podolsky et al, 2016;Zeichner, 2003).…”
Section: Preparing Diverse Sesmentioning
confidence: 99%
“…Wojcik et al. (2023) reported that individuals from diverse backgrounds enter GYOs and alternative licensure programs at higher rates than traditional licensure programs, and alternative programs may successfully attract black men to the teaching profession (Scott, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations